The Clay-like Mechanics Model of Cylindrical Lithium-Ion Battery Cells under Radial Compression. (June 2016) - Wang, WenWei; Yang, Sheng; Sun, FengChun; Yu, QuanQing
Abstract: A simple load case was chosen to reveal the essential mechanics properties of cylindrical lithium-ion battery and it was found that its mechanics characteristic is clay-like, according to the plastic flow rule. Then, a linear equation was proposed to describe the nonlinear constitutive behavior of cylindrical lithium-ion battery, which will lay a foundation for constructing the system of battery mechanics, according to the mechanics characteristic of clay.